Body Mass Index as an Indicator for Endometrial Biopsy in Premenopausal Women with Heavy Menstrual Bleeding - Wafaa Salah Abd-Al Amieer; Lamees Adnan Shubber; Shaymaa Mareai Qaddoori (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Although Obesity is a risk factor of endometrial hyperplasia/ carcinoma, there is no consensus on using the BMI as a predictor for endometrial biopsy screening in patients with heavy menstrual bleeding in pre-menopausal women. Therefore, it’s clinically important to identify BMI cutoff values as a predictor for endometrial hyperplasia/ carcinoma in premenopausal women with heavy menstrual bleeding.Aim of the Study: To determine the feasibility of using Body Mass Index (BMI) as an indicator to perform endometrial biopsy in premenopausal women presented with heavy menstrual bleeding.Patients & Methods: This is a cross-sectional study that was conducted in Obstetrics and Gynecology Clinic /Al-Emamain Al-Kadhemein teaching medical city in Baghdad where women 150 women who are 40-50 years old with heavy menstrual bleeding where sent for endometrial biopsy. 100 women had abnormal endometrial biopsy results, histopathological results of the abnormal endometrial samples were classified into following groups: hyperplasia without atypia, hyperplasia with atypia, and hyperplasia with atypia and cancer. Statistical analysis conducted to correlate The Body Mass Index (BMI) with the status of endometrial biopsy.Results: 42% of the women with BMI≥30 kg/m2 have hyperplasia with atypia or carcinoma compared to 10% of women who BMI<30 kg/m2 (p<0.001). from 54 women who had hyperplasia with atypia in endometrial sample results; 77.7% of such patients were BMI≥30 kg/m2. Receiver operating characteristic analysis shows that using BMI ≥30 kg/m2 as a predictor of hyperplasia with atypia or carcinoma carries a sensitivity of 80.77 % and specify of 86.00% with area under the curve (AUC) value of 0.83 (CI. 0.75-0.92) and (p<0.001). women with BMI≥30 kg/m2 has a relative risk (RR) of 3.98 of developing endometrial hyperplasia (without atypia or with atypia+carcinoma) and a relative risk (RR) of 4.11 of developing hyperplasia with atypia or carcinoma (p<0.001).Conclusion: Our results indicate that BMI regardless of the age is the highest risk factor for abnormal endometrial hyperplasia premenopausal women. Also, BMI≥30 kg/m2 has highest risk for developing endometrial hyperplasia with atypia or carcinoma. BMI≥30 kg/m2 can be used as predictor of endometrial hyperplasia in premenopausal women with heavy uterine bleeding.